Transferrin Receptor-Targeted PEG-PLA Polymeric Micelles for Chemotherapy Against Glioblastoma Multiforme - Sun P (Dove Medical Press, 2020)
Ping Sun,1,2 Yue Xiao,1 Qianqian Di,1 Wenjing Ma,1 Xingyu Ma,1 Qingqing Wang,3 Weilin Chen1 1Guangdong Provincial Key Laboratory of Regional Immunity and Diseases, Department of Immunology, Shenzhen University School of Medicine, Shenzhen 518060, People’s Republic of China; 2Key Laboratory for Biomedical Measurements and Ultrasound Imaging, School of Biomedical Engineering, Shenzhen University Health Science Center, Shenzhen 518060, People’s Republic of China; 3Institute of Immunology, Zhejiang University of Medicine School, Hangzhou, Zhejiang 310058, People’s Republic of ChinaCorrespondence: Weilin ChenGuangdong Provincial Key Laboratory of Regional Immunity and Diseases, Department of Immunology, Shenzhen University School of Medicine, Shenzhen, People’s Republic of ChinaEmail cwl@szu.edu.cnBackground: The safe and efficient delivery of chemotherapeutic agents is critical to glioma therapy. However, chemotherapy for glioma is extremely challenging because the blood–brain barrier (BBB) rigorously prevents drugs from reaching the tumor region.Materials and Methods: TfR-T12 peptide-modified PEG-PLA polymer was synthesized to deliver paclitaxel (PTX) for glioma therapy. TfR was significantly expressed on brain capillary endothelial cells and glioma cells; therefore, TfR-T12 peptide-modified micelles can cross the BBB system and target glioma cells.Results: TfR-T12-PEG-PLA/PTX polymeric micelles (TfR-T12-PMs) could be absorbed rapidly by tumor cells, and traversed effectively the BBB monolayers. TfR-T12-PMs can effectively inhibit the proliferation of U87MG cells in vitro, and TfR-T12-PMs loaded with paclitaxel presented better antiglioma effect with prolonged median survival of nude mice-bearing glioma than the unmodified PMs.Conclusion: The TfR-T12-PMs could effectively overcome the BBB barrier and accomplish glioma-targeted drug delivery, thus validating its potential in improving the therapeutic outcome in multiforme.Keywords: polymeric micelles, transferrin receptor, BBB transcytosis effect, glioblastoma multiforme, targeted delivery